Treatment strategy, overall survival and associated risk factors among patients with unresectable stage IIIB/IV non-small cell lung cancer in China (2015–2017): A multicentre prospective study - Yuankai Shi; Xin Zhang; Gang Wu; Jianping Xu; Yong He; Dong Wang; Cheng Huang; Mingwei Chen; Ping Yu; Yan Yu; Wei Li; Qi Li; et al. (The Lancet Regional Health. Western Pacific, 2022)
Summary: Background: There are limited studies on treatment and survival analysis among patients with unresectable Stage IIIB or IV non-small cell lung cancer (NSCLC) in routine practice in China. To address this gap, we conducted a prospective observational study in a cohort of patients treated at 11 hospitals in China. Methods: This was a multicentre, prospective cohort study including patients with newly diagnosed unresectable Stage IIIB or IV NSCLC from June 26th, 2015 to April 28th, 2017. Patient baseline characteristics, disease characteristics, and anti-cancer treatments were obtained by medical chart review. The overall survival (OS) from the initiation of first-line treatment was analysed by the Kaplan-Meier method. Factors associated with survival were analysed by univariate and multivariate Cox regression models. Findings: Among 1324 patients enrolled with median follow-up duration of 15·0 (range: 0·0–42·1) months, 83·5% (1105/1324) of them received first-line chemotherapy of which platinum-based compounds were the dominated agents. Overall, 30·9% (409/1324) of patients received targeted therapy as 1st-line treatment including 65·0% (266/409) EGFR-TKIs and 5·1% (21/409) ALK-TKIs. Of all eligible patients, gene testing rates were 44·0% (583/1324) for EGFR mutations, 17·0% (225/1324) for EML4-ALK gene fusions, and 8·3% (110/1324) for ROS1 gene fusions. The EGFR-TKIs were administered to 63·9% (179/280) of EGFR mutated patients as first-line treatment. The overall median OS was 23·2 (95%CI 19·5-25·5) months, and patients treated at tier 1 cities had better OS than that of tier 2 cities. Also, the OS in patients with EGFR mutation was longer than those with EGFR wild type. Multivariate Cox regression models suggested that male, education below high school, tier 2 cities, smoking history, and multiple metastases were associated with poor survival. Interpretation: The gene test coverage was relatively low among the studied population, and over half of EGFR mutated patients received EGFR-TKIs, suggesting that the result of genetic tests in real-world settings may not always indicate the selection of treatment. The OS benefit observed from patients treated in tier 1 cities and those with EGFR mutation may indicate a need for broader gene test coverage, providing NSCLC patients with personalized treatment according to the results of genetic tests. Funding: Roche Holding AG.TRANSLATED ABSTRACT: This translation in Chinese was submitted by the authors and we reproduce it as supplied. It has not been peer reviewed. Our editorial processes have only been applied to the original abstract in English, which should serve as reference for this manuscript.摘要背景介绍:目前针对中国不可切除的IIIB期或IV期非小细胞肺癌(NSCLC)患者在临床实践中的治疗模式和生存分析的研究有限.为了填补这一空白, 我们开展了一项前瞻性,观察性研究, 纳入来自11家医院的患者.方法:这是一项多中心,前瞻性队列研究, 纳入了2015年6月26日至2017年4月28日新诊断为不可切除的IIIB期或IV期NSCLC患者.通过病历筛查获得基线特征,临床肿瘤特征和抗肿瘤治疗.采用Kaplan-Meier法分析从开始一线治疗后的总生存期(OS), 并通过单因素和多因素Cox回归模型分析与生存相关的影响因素.结果:在入组的1324例患者中, 中位随访时间为15.0个月(范围:0.0-42.1), 其中83.5%(1105/1324)的患者接受了一线化疗, 以铂类化合物为主.总体而言, 30.9%(409/1324)的患者接受靶向治疗作为一线治疗, 其中包括65.0%(266/409)的患者接受了EGFR-TKI治疗和5.1%(21/409)的患者接受了ALK-TKI治疗.在所有符合条件的患者中, EGFR突变,EML4-ALK基因融合和ROS1基因融合的基因检测率分别为44.0%(583/1324),17.0%(225/1324)和8.3%(110/1324).63.9%(179/280)的EGFR突变患者接受EGFR-TKI作为一线治疗.全组患者的中位总生存期为23.2 (95%置信区间 19·5-25·5) 个月, 在一线城市治疗的患者的总生存期优于二线城市的患者.此外, EGFR突变患者的总生存期长于EGFR野生型患者.多因素Cox回归模型分析表明, 男性,高中以下文化程度,二线城市,吸烟史及肿瘤转移与较低的生存率相关.解释:本研究人群中的基因检测覆盖率相对较低, 其中超过一半的EGFR突变患者接受了EGFR-TKI治疗, 这表明在真实世界诊疗中, 基因检测的结果可能并不完全指导治疗选择.总生存期在一线城市接受治疗的患者和EGFR突变的患者中更佳的现象, 可能提示需要更广泛的基因检测覆盖, 并根据基因检测结果为NSCLC患者提供个体化治疗.